Effect of hematuria on the outcome of immunoglobulin A nephropathy with proteinuria - Chihiro Iwasaki; Takahito Moriyama; Kayu Tanaka; Takashi Takei; Kosaku Nitta (Society of Diabetic Nephropathy Prevention, 2016)
Background:The relationship between hematuria and histological lesions, the effect of hematuria on response to steroid therapy, and the outcome in patients with immunoglobulin A nephropathy (IgAN) remain undetermined. Objectives: The aim of this study was to clarify the effect of hematuria on histological findings, response to steroid treatment, and the outcome in IgA nephropathy. Patients and Methods: Seventy-five patients with IgAN and proteinuria > 1 g/day and treated with prednisolone were divided into two groups: those with low (≤20/high-power field [HPF]) urinary red blood cell (U-RBC) counts (L-RBC group, n=55) and those with high (>20/HPF) U-RBC counts (H-RBC group, n=20). Their clinical and histological characteristics, the relationship between hematuria and histological lesions, renal outcomes, and risk factors for progression were compared. Results: Except for U-RBC counts, the clinical and histological findings according to the Oxford classification of the two groups were similar. U-RBC counts were not correlated with active histological lesions. Median proteinuria in both groups decreased soon after starting steroid therapy. Median U-RBC also decreased after starting steroids, and it became similar between both groups at 2 years after treatment. The 20-year renal survival rate was also similar between the H-RBC and the L-RBC group (45.2% versus 58.0%, P=0.5577). Multivariate Cox regression analysis showed that the lower estimated glomerular filtration rate (eGFR) was an independent risk factor for progression. Conclusions: A higher degree of hematuria at renal biopsy in patients with IgAN was not associated with active pathological lesions, such as cellular and fibro-cellular crescents, resistance to steroid treatment and poor outcome.